Teacher as a Transformer of Cognitive and Wisdom for Sustainable Character Development - Retno Wiratih, Hernawati W. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2017)
Development of character virtue is the key to personal, academic, and professional success in life. Today, we face enormous challenges in educating of young people, who provide youth with basic academic, knowledge and skills, accordingly, promote their character development. Modern global culture suffers from a variety of negative trends which are reflected and reinforced in the world of education. These challenges include a perceived decline in the value of intelligence, complex thought, wisdom of superficiality in favor, and the loss of intellectual and moral standards. These conditions will affect their mindset, attitude and behavior that will eventually form of character of individual and community and so will be affected to the society life, especially the characters of young generation. According to Rosenshine and Stevens, 1986, teaching behavior correlate with the student performance to support and develop student’s self-identity. Historically, schools have always had responsibility for both academic and character development. Regarding education’s wisdom, students need to develop “learning strategies” that support their life-long learning. To do so, education today should facilitate the development of interpretative skills, deep understanding to face and solve the complex problems. Performance of professional teachers must be raised and clearly existence of knowledge by aggregation of skills, technology, and ethics disposition